THE NEW RANK ONE CLASS FOR UNCONSTRAINED PROBLEMS SOLVING - Ahmed Mustafa (Science Journal of University of Zakho, 2023)
One of the most well-known methods for unconstrained problems is the quasi-Newton approach, iterative solutions. The great precision and quick convergence of the quasi-Newton methods are well recognized. In this work, the new algorithm for the symmetric rank one SR1 method is driven.